Upaya Meningkatkan Keterampilan Berbicara Siswa Menggunakan Metode Pembelajaran Show And Tell Pada Siswa Kelas IV UPT SDN 20 Binamu Kabupaten Jeneponto - Rosdiah Salam; Andi Dewi Riang Tati; Nurmuthia Arfah (Universitas Negeri Makassar, 2023)
The problem in this research is the low speaking skills of fourth grade students of UPT SDN 20 Binamu, Jeneponto Regency. This study aims to improve students' speaking skills using the Show and Tell learning method in class IIV UPT SDN 20 Binamu Jeneponto Regency. The approach used in this study is a descriptive qualitative approach. This type of research is Classroom Action Research (CAR). The focus of this research is the use of the Show and Tell method and improving speaking skills using the Show and Tell method. The setting for this research is UPT SDN 20 Binamu, Jeneponto Regency, for the 2022/2023 academic year. The research subjects were teachers and fourth grade students of UPT SDN 20 Binamu, Jenenponto Regency, with a total of 26 students consisting of 15 15 girls and 11 boys. Data collection techniques used are observation, tests and documentation. The data analysis technique used is a qualitative data analysis technique. The results showed that there was an increase in students' speaking skills, namely in cycle I it reached 74.42 and the percentage of classical learning completeness was 73.07%. In cycle II the average value increased to 83.88 and the percentage of classical learning completeness became 84.61%. As for the learning activities, the achievement of students in cycle I was in the sufficient category (C), while the achievements in cycle II were in the very good category. The final test of speaking skills in cycle I was in the good category (B) while in cycle II it was in the very good category. From the results of this analysis it can be concluded that through the use of the Show and Tell learning method it can improve speaking skills in class IV students of UPT SDN 20 Binamu, Jeneponto Regency.